PERBEDAAN ANCAMAN PIDANA BAGI PELAKU LIWAT DEWASA TERHADAP ANAK-ANAK (KAJIAN AYAT (3) PASAL 63 QANUN JINAYAT NO. 6 TAHUN 2014) - ASTUTI, ASTUTI (State Islamic University (UIN) Ar-Raniry, 2016)
This paper aimed to describe the view of Qanun Jinayat (Criminal Acts Regional Bylaws) No. 6/2014 Article 63 on the perpetrators of liwat (sodomy) between adults with adults and adults with children as well as the ta'zir (punishment administered at the discretion of the judge) that exceeded hudud (punishment for certain offenses that are fixed by the Qur'an or Hadith). The results showed that Qanun Jinayat differentiated the two types of liwat perpetrators because the adults’ penalties have been stipulated in the Sharia law with obvious penalties as in adultery. On the other hand, the perpetrators committing liwat against children were subject to extraordinary violation of Sharia. Therefore, the perpetrators were punished twice as much. The ta'zir penalty may have exceeded the hudud under the basis of the Hadith and also the rules of fiqh (Islamic jurisprudence).